The Causes Analysis of Pulmonary Function Disorders at Semen X Company - Sunarsieh, Sunarsieh; Permatasari, Eno; Hermilestari, Ani (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Abstract. The cement industry is the largest manufacturing industry, vital for sustainable development, and very risky for workers to be exposed to dust in various processes, including production. Continuous exposure to dust can cause pulmonary function disorders. This study aimed to analyze the relationship between dust exposure, age, length of work, working period, use of PPE (masks), smoking habits, and pulmonary function disorders in labor. This research used an observational method with a cross-sectional approach. The research sample was a total population of 38 male workers at Semen X company, engaged in the cement bagging industry as business activities. Data collection was by interviewing respondents, measuring the level of inhaled dust with a personal dust sampler, and checking the lung capacity with a spirometer. Data analysis was performed bivariate with the chi-square test. The results showed that there was a relationship between the use of PPE (mask) (p = 0.006) with pulmonary function disorders.